Dopamine Receptor Subtypes, Physiology and Pharmacology: New Ligands and Concepts in Schizophrenia - Martel, Jean Claude; Gatti McArthur, Silvia (Frontiers in Pharmacology, 2020)
Dopamine receptors are widely distributed within the brain where they play critical modulatory roles on motor functions, motivation and drive, as well as cognition. The identification of 5 genes coding for different dopamine receptor subtypes, pharmacologically grouped as D1- (D1 & D5) or D2-like (D2S, D2L, D3 and D4) has allowed the demonstration of differential distribution in within brain structures, this being likely associated to functional differences. Recent advances on dopamine receptor function in the brain still point at D2-like receptors as the most relevant therapeutic target for schizophrenia and for the development of antipsychotics. D2-like receptors are concentrated within the caudate and putamen with moderate densities throughout cortical structures. Progress in the chemistry of D2-like receptor ligands-antagonists and -partial agonists have provided more selective compounds possibly relevant to study the specific physiological roles of these receptor subtypes in relation to different schizophrenia symptoms. Moreover, an extensive evaluation of the functional effect of these agents on dopamine receptor coupling and intracellular signaling highlights important differences that could also result in highly differentiated clinical pharmacology. The review summarizes the recent advances in the field addressing the relevance of emerging new targets in schizophrenia research in relation to the dopamine neurocircuitry.